Female foeticide: a social menace - Farooqui, Jamil (Radiance Viewsweekly, 2010)
Women have been the subject of deprivation, discrimination, intimidation, and unjust treatment in society throughout history. The difference is only in the forms that differ from time to time and from society to society. Women are considered inferior, given secondary status, subjugated to the male, subjected to various ordeals and deprived of the basic right of existence. They are considered persons whose duty is to act on the advice of males, serve them, please and take care of them: first father, then husband then son. They are given such an ideal role as to live at the mercy of the husband and die at his pyre. The reason is that in the social fibre of many societies males are given a privileged position because they are bread-winners, feed the family, and continue the name of the family. Women are the commodities at the disposal of males, whenever and however they want to use them. Thus, they are in a subordinate position, do not represent an independent entity, have no control over their lives, and do not stand on their own dignity, but constitute the amour propre of others.....